Respuesta :
Answer:
0, -2
Step-by-step explanation:
x/2 = x²/(x-2)
x² - 2x = 2x²
x² + 2x = 0
x(x + 2) = 0
x = 0, -2
0/2 = 0²/(0-2)
0 = 0
-2/2 = (-2)²/(-2-2)
-1 = 4/-4
-1 = -1
Solving the rational equation x/2 = x²/(x - 2) is;
The rational equation can be written mathematically as;
x/2 = x²/(x - 2)
By cross product;
x² - 2x = 2x²
x² + 2x = 0
x (x + 2) = 0.
x = 0 or x = -2.
To check for extraneous solutions;
For x=0;
- 0/2 = 0²/-2
- 0 = 0
For x = -2;
- -2/2 = (-2)²/(-2-2)
- -1 = 4/-4
-1 = -1.
Read more:
https://brainly.com/question/14049952